INOVASI DALAM METODE DAN MODEL PEMBELAJARAN BAHASA INDONESIA DI TINGKAT SEKOLAH DASAR - Santi Awaliatul Zahro; C Alfa Zahra; Nurfitria (CV. ADIBA AISHA AMIRA, 2025)
Learning methods are a set of methods, efforts, and strategies used by educators so that students can achieve learning goals or master certain competencies formulated in the syllabus. Therefore, it is necessary to choose the right learning method or model for students because the learning method functions as a strategy to achieve the goals of learning activities. It is hoped that teachers can coordinate with what learning methods and models are effective and efficient with Indonesian learning in elementary school. Therefore, the author has tried to research related information, using library or literature research methods through various sources. The goal is for educators to master and understand various kinds of learning methods and models that can be carried out or applied. And from the results of this library research method, it has contributed to finding various learning methods and models that can be applied to Indonesian learning in elementary school.